1992
DOI: 10.1128/aac.36.1.71
|View full text |Cite
|
Sign up to set email alerts
|

High-level beta-lactamase activity in sputum samples from cystic fibrosis patients during antipseudomonal treatment

Abstract: The in vivo activity and source of I-lactamase in sputum samples from 43 patients with cystic fibrosis (CF) during a 2-week antipseudomonal treatment were studied. A colorimetric method, based on the conversion of nitrocefin, was used for quantitation of the sputum ,B-lactamase activity. P-Lactamases in sputum were characterized by isoelectric focusing and inhibition profile and were compared with the ,-lactamases extracted from Pseudomonas aeruginosa isolated from the paired sputum samples. We found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 14 publications
4
40
0
Order By: Relevance
“…This study has clearly demonstrated highlevel beta-lactamase activity in sputum samples from cystic fibrosis patients during antipseudomonal treatment. 27 This study further propose and support the hypothesis that b-lactamase production is an important in vivo resistance mechanism in infected patients which could subsequently lead to more severe inflammation and scaring formation. Aspartoacylase-3 reported to localize to the cytoplasm of S2 and S3 proximal tubules and to the apical domain of S1 proximal tubules 28 and may function as an hepatitis C virus (HCV) core binding protein which may play a role in the development of HCV-associated diseases.…”
Section: Discussionsupporting
confidence: 66%
“…This study has clearly demonstrated highlevel beta-lactamase activity in sputum samples from cystic fibrosis patients during antipseudomonal treatment. 27 This study further propose and support the hypothesis that b-lactamase production is an important in vivo resistance mechanism in infected patients which could subsequently lead to more severe inflammation and scaring formation. Aspartoacylase-3 reported to localize to the cytoplasm of S2 and S3 proximal tubules and to the apical domain of S1 proximal tubules 28 and may function as an hepatitis C virus (HCV) core binding protein which may play a role in the development of HCV-associated diseases.…”
Section: Discussionsupporting
confidence: 66%
“…Preexisting subpopulations with stable, partially derepressed AmpC may thus rapidly expand under treatment with agents such as ceftazidime, piperacillin, or imipenem (17). Partial release of their ␤-lactamase content in sputum samples could contribute to antibiotic inactivation in situ (18). Whether these partially derepressed mutants would provide more susceptible bacterial populations with efficient protection against ␤-lactams is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Some data indeed suggest that in nfxB mutants, the enzyme AmpC leaks out of the cells and concentrates in the surrounding milieu rather than in the periplasm, thus generating whole protection for cells of the biofilm (472). This may be relevant in vivo, as important extracellular AmpC activities have been measured in the sputa of cystic fibrosis patients (473). Whereas the mexXY genes (and their products) are expressed at similar levels in nfxB mutants and wild-type strains, MexCD-OprJ appears to compromise the MexXY/OprM(OprA) drug transport activity and associated resistance to aminoglycosides by downmodulating the production of the protein OprM (472).…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%